Introduction to the Special Issue "There is a Crack in Everything-Education and Religion in a Secular Age" - K. H. (Ina) (MDPI AG, 2019)
The seemingly paradoxical contrast between an expected decline of religion in the public domain and an increase of the importance of religiosity and spirituality in people’s lives, led Peter Berger to revisit his prophecy about secularisation [...]